Vascularized Osteomyocutaneous Allografts Are Permissive to Tolerance by Induction‐Based Immunomodulatory Therapy. Issue 8 (29th May 2013) - Lin, C. H.; Zhang, W.; Ng, T. W.; Zhang, D.; Jiang, J.; Pulikkottil, B.; Lakkis, F.; Gorantla, V. S.; Lee, W. P. A.; Brandacher, G.; Zheng, X. X.
Abstract: Vascularized composite allografts (VCAs) are unique among transplanted organs in that they are composed of multiple tissues with disparate antigenic and immunologic properties. As the predominant indications for VCAs are non‐life‐threatening conditions, there is an immediate need to develop tolerance induction strategies and to elucidate the mechanisms of VCA rejection and tolerance using VCA‐specific animal models. In this study, we explore the effects of in vitro induced donor antigen‐specific CD4 − CD8 − double negative (DN) Treg‐based therapy, in a fully MHC mismatched mouse VCA such as a vascularized osteomyocutaneous as compared to a non‐VCA such as a full thickness skin (FTS) transplantation model to elucidate the unique features of VCA rejection and tolerance. We demonstrate that combined therapy with antigen‐induced CD4 derived DN Tregs and a short course of anti‐lymphocyte serum, rapamycin and IL‐2/Fc fusion protein results in donor‐specific tolerance to VCA, but not FTS allografts. Macrochimerism was detected in VCA but not FTS allograft recipients up to >60 days after transplantation. Moreover, a significant increase of CD4 + Foxp3 + Tregs was found in the peripheral blood of tolerant VCA recipients. These data suggest that VCA are permissive to tolerance induced by DN Treg‐based induction therapy. Abstract : This study demonstrates that vascularized osteomyocutaneous allografts are permissive to tolerance by inductionbased immunomodulatory therapy, and ex vivo alloantigen‐induced CD4+ T cell—derived DN Tregs may provide an opportunity to develop novel strategies for transplant tolerance.